GAYA KEPEMIMPINAN KEPALA SEKOLAH DALAM PEMBENTUKAN KARAKTER RELIGIUS PESERTA DIDIK (Studi Pada Sekolah Dasar Islam Terpadu Insan Qur'ani) - Alia Rismayanti; Dedi Supriadi (Jurnal Ekonomi & Bisnis, 2026)
This study analyzes the leadership style of the Principal of SDIT Insan Qur'ani in forming the religious character of students. The urgency of this research is motivated by the importance of the role of principal leadership in forming religious character in the digital era full of moral challenges. The purpose of this study is to identify the leadership styles applied, analyze their implementation, and evaluate their effectiveness in shaping students' religious character. The research method uses a descriptive qualitative approach with data collection techniques through in-depth interviews, observation, and documentation. The results of this study indicate that the principal's transformational leadership style has proven effective in shaping the religious character of students at SDIT Insan Qur'ani. This transformational leadership style was manifested through four main dimensions, namely idealized influence, inspirational motivation, intellectual stimulation, and individual consideration. This transformational leadership style was implemented through various religious programs and activities, mentoring, and collaboration with parents. The effectiveness of the principal's transformational leadership style is proven by the improvement in the quality of students' religious character, as seen in aspects of religious discipline, Qur'anic skills, moral improvement, and achievements in religious competitions. Despite facing several challenges such as time constraints, differences in student backgrounds, the influence of social media, and limited infrastructure, the religious character building program can run smoothly with the commitment of the principal, teacher support, and parental participation.